The Effects of Fluctuations of Oil Price on Economic Growth of Libya - Aimer, Nagmi M. Moftah (Asian Economic and Social Society, 2016)
Since the first oil price fluctuation in 1973s, macroeconomists have viewed sharp movements in the price of oil are generally as an important source of economic fluctuations. Furthermore, the very recent highs registered in the? crude oil market are causing concern about possible slowdowns in the economies of many developed countries and it has a significant role in the economic growth of Libya. The purpose of this study is to investigate the effect of fluctuations in oil prices on Libya?s economic growth. This is achieved by the use of (VAR) modal and co-integration techniques. In this respect, the relation between two variables will be analyzed by using annual data from 2000 to 2015. The results indicate that both series are integrated of order one I (1), having a long-term relationship between crude oil price and growth. The estimates suggest that higher oil price has a positive and statistically important impact on the economic growth of Libya.
Keywords: 8. Economic growth; 1. No poverty